Eficiencia química del nitrógeno aplicado para la producción de quinua dulce (Chenopodium quinoa Willd.) variedad INIAP pata de venado en Laguacoto III, provincia Bolívar - Morales Velasco, Grey Mariela (2024)
Quinoa currently has a global interest and is positioned in different research processes in the value chain segments due to its resilience to climate change and its excellent nutritional quality. It is native to the Andean Zone and Ecuador is cultivated in the provinces of the highlands. The province of Bolívar has a potential for this crop which would contribute to the diversification and greater efficiency of production systems, however, producers are unaware of the benefits and technological alternatives of this crop, which is key to food security. This research was carried out in the Laguacoto III Farm of the Guaranda canton, province of Bolívar at an altitude of 2640 m. The objectives were to combine the main agronomic characteristics of the variety INIAP Pata de Venado with the application of four doses of nitrogen and calculate the Relation Benefit - Cost (RB / C). The experimental design of Complete Random Blocks was applied with four doses of nitrogen (10; 40; 80 and 120 kg/ha), with three repetitions. Performance components were evaluated. Analyses of variance, Tukey's test, correlation, regression and RB/C were calculated. A significant effect of the results in the main variables evaluated was determined in response to the four doses of N, the most efficient being 80 kg/ha with an average yield of 1959 kg/ha and an RB/C of 0,19. The components that increased the yield were days at harvest, height of plants, length and diameter of the panicles, weight of one hundred grains and grain size. Finally, this study determined the agronomic adaptation of INIAP Pata de Venado in the territory of Laguacoto III and its greater chemical efficiency with the dose of 80 kg / ha of nitrogen.